Stab-resistance improvement of short carbon fiber reinforced UHMWPE knitted composites with plasma/oxidation treatment. (29th September 2022) - Liu, Qing; Wang, Lanlan; Luo, Qin; Sun, Zhaoling; He, Haijun; Chen, Chaoyu; Ma, Pibo
Two modification methods, including low temperature plasma treatment and HNO3 oxidation, used to modify double-layer knitted fabric (DLKF) with UHMWPE yarn and CFs respectively. Contact angle, Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM) are used to evaluate the modification effect of the fabric or CFs. Epoxy resin (ER) is used as adhesive to prepare composite, and the effect of modification on the stab resistance is further studied through the test of stab resistance. In addition, the damage mechanism of DLKF and R-DLKF are analyzed. The results showed that the plasma treatment has a great effect on the modification of DLKF. After 15–20min of modification, the stab resistance of the composite is the best. The peak load and energy can be increased by about 19.1% and 23.1%. HNO3 oxidation has a great effect on the modification of CFs, the stab-resistance of CFs reinforced DLKF (R-DLKF) can be improved by about 17.3% after being treated with 60% HNO3 for 24h. DLKF fails mainly due to the stretching and cutting action of the yarn. Fabric as matrix can prevent crack propagation further, and the shear force, yarn cutting and pullout action within the composite is the key to improve the stab resistance. This work opens up the possibilities for the industrial production of personal protection products and devices, which is expected to provides a reference for the modification of fabrics and fibers in the production of composite.